Hyperbranched polyester polyol plasticized tapioca starch/low density polyethylene blends (2017)
ABSTRACT: In this work, low density polyethylene (LDPE)/plasticized starch (TPS) blends were prepared. The TPS employed in this study was obtained by plasticization of tapioca starch with a hyperbranched polyester polyol. Differential scanning calorimetry analysis showed that the melting temperature increased with the TPS content. The opposite effect was exhibited in the crystallization temperature and additional changes were not observed during the heating. X-ray diffraction analysis showed a reduction in intensity of the peak at Bragg’s angle 17.5°, proving a diminution on A type crystallinity with the increasing amount of LDPE. Micrographs obtained by scanning electron microscopy exhibited starch granules without destructure. TPS acted as a filler to LDPE, since the mechanical properties (Young’s modulus and tensile strength) improved ostensibly. The Young’ modulus and tensile strength decreased with the amount of LDPE, however, the elongation at break exhibited an opposite behavior.